A psychosocial reading of novice clinical psychologists' talk about whiteness,Psychological reading of novice clinical psychologists' talk about whiteness - Kennedy, Brink (Rhodes University, Faculty of Humanities, Department of Psychology, 2018)
This research presents a case study report of interview encounters with two novice white South African clinical psychologists. A psychosocial research methodology is employed to examine the discursive strategies that participants engage in when speaking about whiteness in the context of their professional identity and practice, as well as to examine the ways in which these discursive strategies support or constrain 'mentalizing' in relation to raced experience. One case study highlights an individualistic discourse of 'racial innocence', which constructs the speaker as being free of racial enculturation and consciousness, eliding a broader social context. I argue that this discourse closes down mentalizing in relation to more difficult, intractable aspects of raced experience in clinical work, relating to differences in positionality as well as issues of inequality. I also propose that this discourse may be understood in terms of a 'pretend' mode of thought, where aspects of the wider social context and of race in particular are experienced as being unrelated to intimate personal experience. The other case study highlights a discourse of 'uneasy whiteness' that involves awareness of white positionality, and that is grounded in a constructionist sensibility. This positions the speaker as being inevitably implicated in white privilege and racism in ways that she may be ignorant of. I argue that the discourse facilitates a particular type of mentalizing that is sensitive to the interpellation of intimate personal experience with a wider social context that encompasses a range of discourses and practices. It closes down mentalizing, however, in so far as it allows a reified construction of whiteness. I find the concept of psychic equivalence, which equates external (concrete, factual) reality and internal (subjective, symbolic) reality, useful in terms of understanding this reification. Overall the research highlights the tension between constructionist and individualistic modes of thinking within clinical psychology research and practice in the South African context. At the level of methodology, it presents an example of how these modes may be integrated within research. At the level of content, it explores differences between constructionist and individualistic talk in relation to race and psychological practice.
Keywords: Clinical psychology Practice -- South Africa; White people Race identity -- South Africa; White privilege (Social structure) -- South Africa; White people Race identity Psychological aspects; Intercultural communication; Psychoanalysis and racism -- South Africa; Mentalization Based Therapy